Two-dimensional metal-organic frameworks: from synthesis to bioapplications - Weiqi Wang (Journal of Nanobiotechnology, 2022)
Abstract As a typical class of crystalline porous materials, metal–organic framework possesses unique features including versatile functionality, structural and compositional tunability. After being reduced to two-dimension, ultrathin metal-organic framework layers possess more external excellent properties favoring various technological applications. In this review article, the unique structural properties of the ultrathin metal-organic framework nanosheets benefiting from the planar topography were highlighted, involving light transmittance, and electrical conductivity. Moreover, the design strategy and versatile fabrication methodology were summarized covering discussions on their applicability and accessibility, especially for porphyritic metal-organic framework nanosheet. The current achievements in the bioapplications of two-dimensional metal-organic frameworks were presented comprising biocatalysis, biosensor, and theranostic, with an emphasis on reactive oxygen species-based nanomedicine for oncology treatment. Furthermore, current challenges confronting the utilization of two-dimensional metal-organic frameworks and future opportunities in emerging research frontiers were presented. Graphical Abstract